Developing a digital currency from an Islamic perspective: the case of blockchain technology - Alzubaidi, Ibrahim Bassam; Abdullah, Adam (Canadian Center of Science and Education, 2017)
Numerous studies ranging from concept papers and reviews were conducted on the matter of blockchain and digital currencies. However, those two areas are not well researched due to its being a new area of research. Furthermore, the research on blockchain applications in the Islamic financial system precisely the potential of digital currency in providing a better alternative to current fiat money system which will be the scope of this article. The aim of revolves around exploring the potential and capability of introducing a digital currency that fulfills the Islamic law (Shari’ah) functions of money and provides a more stable currency than fiat money. The method used for analyzing this object includes a library research on related topics that helps understanding the functions of money and digital currencies and study of several cases that can assist in fulfilling the objectives of this paper in introducing an Islamic digital currency through detailed research of Islamic theory of money and civilization as well as the developments of blockchain, our findings point towards the ability of introducing a Shari’ah-compliant digital currency if all the issues on validity are addressed and resolved. However, the area of digital currencies and blockchain requires further research from a Shari’ah perspective to facilitate a better understanding on the topic.